2018
DOI: 10.1002/acn3.566
|View full text |Cite
|
Sign up to set email alerts
|

Navigational cue effects in Alzheimer's disease and posterior cortical atrophy

Abstract: ObjectiveDeficits in spatial navigation are characteristic and disabling features of typical Alzheimer's disease (tAD) and posterior cortical atrophy (PCA). Visual cues have been proposed to mitigate such deficits; however, there is currently little empirical evidence for their use.MethodsThe effect of visual cues on visually guided navigation was assessed within a simplified real‐world setting in individuals with tAD (n = 10), PCA (n = 8), and healthy controls (n = 12). In a repeated‐measures design comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 50 publications
3
30
0
Order By: Relevance
“…Posterior cortical atrophy (PCA) is conventionally defined as a syndrome characterized by progressive impairment of higher visual function, in particular visuoperceptual and visuospatial skills, often designated the 'visual variant' of Alzheimer's disease (Benson et al, 1988;Crutch et al, 2017). Patients with PCA have particular difficulty interpreting and navigating 'busy', dynamic visual environments requiring parsing of multiple objects distributed in space (Shakespeare et al, 2013;Yong et al, 2018). Posterior cortical functions such as calculation, spelling and praxis are also affected in PCA (Benson et al, 1988;Crutch et al, 2017), along with other cognitive domains including language (Crutch et al, 2013), episodic memory (Ahmed et al, 2018), working memory (Trotta et al, 2019), executive functioning (Putcha et al, 2018), and visuo-vestibular integration (Crutch et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Posterior cortical atrophy (PCA) is conventionally defined as a syndrome characterized by progressive impairment of higher visual function, in particular visuoperceptual and visuospatial skills, often designated the 'visual variant' of Alzheimer's disease (Benson et al, 1988;Crutch et al, 2017). Patients with PCA have particular difficulty interpreting and navigating 'busy', dynamic visual environments requiring parsing of multiple objects distributed in space (Shakespeare et al, 2013;Yong et al, 2018). Posterior cortical functions such as calculation, spelling and praxis are also affected in PCA (Benson et al, 1988;Crutch et al, 2017), along with other cognitive domains including language (Crutch et al, 2013), episodic memory (Ahmed et al, 2018), working memory (Trotta et al, 2019), executive functioning (Putcha et al, 2018), and visuo-vestibular integration (Crutch et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Controls were clearly able to anticipate the corners and walked with an efficient smooth path around the corners, but some participants in the dementia groups did not demonstrate the same anticipation. Either they were not able to efficiently interpret or act on the visual information, due to low visual orientation or visuomotor/visual processing impairments, or were unable to predict layouts of routes due to diminished topographical processing, spatial memory and/or executive function [26]. Future investigations might explore the relationship between gait dynamics, spatial memory and route learning abilities.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore particularly beneficial to be able to use standardised algorithms to process step data. In the context of research into dementia friendly environments, the effects of perceptual environmental variables, such as lighting, visual cues and clutter on patient navigation can be evaluated in a variety of scenarios [26].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations PCA is a progressive neurodegenerative disease characterized by visuospatial or visuoperceptual symptoms with relative sparing of memory (see Table 3). [65][66][67][68][69][70][71] PCA patients could have significant impairment of everyday skills and self-care. 72 Patients often complain of having blurred or obscured vision.…”
Section: Pca Variant Of Admentioning
confidence: 99%
“…113 In another study, Yong et al demonstrated that the use of visual cues can improve the ability of PCA patients to reach another destination in a closed-space setting. 70…”
Section: Management and Treatmentmentioning
confidence: 99%